Operating metaphor of the concept of love in Shams (Based on the theory of Lakoff and Johnson) - مختاری مسروره; آلیانی رقیه (LANGUAGE ART, 2019)
Language is one of the most important human achievements to transfer thoughts and concepts. From the viewpoint of Cognitive Linguists, language is a tool to communicate everyone’s perceptual and cognitive system. Accordingly, poets and writers, especially mystics have applied language in a particular way so that it inspires cognitive, metaphysic, mystic and romantic concepts; also, they planned their themes by using language processes such as conceptual metaphor. Conceptual metaphor, at first developed by Lakoff and Johnson in the book “Metaphors We Live By”, is based on mind and experience. Lakoff believes that the themes of the human mind are fundamentally metaphoric, and even they are appeared through everyone’s daily life. As mysticism especially Mawlana’s mysticism is derived from his mystical experiences based on personal experiences, the present research has utilized the theory of Conceptual Metaphor by Lakoff and Johnson, based on types of metaphor and image schema for identifying the ideological themes of Mawlana by using a descriptive-analytic approach. In this paper, the conceptual metaphor of Love in animal symbols of Shams lyrics was propounded in two sections of schema and metaphor types. The results of the research suggest that the conceptual metaphor of Love represented in the two groups of force and path schema, and according to the types of metaphor, they are represented in the form of structural and orientation conceptual metaphors.